Face, content, and construct validity of a virtual reality otoscopy simulator and applicability to medical training - Albrecht, Tobias; Nikendei, Christoph; Praetorius, Mark (Otolaryngology - head and neck surgery, 2022)
ObjectiveOtologic diseases are common in all age groups and can significantly impair the function of this important sensory organ. To make a correct diagnosis, the correct handling of the otoscope and a correctly performed examination are essential. A virtual reality simulator could make it easier to teach this difficult-to-teach skill. The aim of this study was to assess the face, content, and construct validity of the novel virtual reality otoscopy simulator and the applicability to otologic training.Study DesignFace and content validity was assessed with a questionnaire. Construct validity was assessed in a prospectively designed controlled trial.SettingTraining for medical students at a tertiary referral center.MethodThe questionnaire used a 6-point Likert scale. The otoscopy was rated with a modified Objective Structured Assessment of Technical Skills. Time to complete the task and the percentage of the assessed eardrum surface were recorded.ResultsThe realism of the simulator and the applicability to medical training were assessed across several items. The ratings suggested good face and content validity as well as usefulness and functionality of the simulator. The otolaryngologists significantly outperformed the student group in all categories measured (P < .0001), suggesting construct validity of the simulator.ConclusionIn this study, we could demonstrate face, content, and construct validity for a novel high-fidelity virtual reality otoscopy simulator. The results encourage the use of the otoscopy simulator as a complementary tool to traditional teaching methods in a curriculum for medical students.